Development of an equipment for real-time continuous monitoring of alpha and beta radioactivity in river water. (September 2022) - Tarancón, A.; Novella, O.; Pujadas, M.; Batlle, M.; Cros, J.; García, J.F.
Abstract: Different regulations require the monitoring of radioactivity in the environment (e.g., 2013/51/Euratom, Real Decreto 314/2016) to protect the environment and the population from abnormal radioactivity presence caused by natural reasons or discharges or accidents in nuclear installations. Nowadays, the monitoring of α- and β-emitting radionuclides is performed discontinuously in laboratories due to the difficulties in applying classical techniques to continuous measurements. This limits the number of samples that can be measured per day, produces high costs per analysis, and introduces a significant delay between the moment of contamination and when it is detected. Plastic scintillation microspheres (PSm) represent a new possibility for continuous measurements because water samples can flow through a bed of PSm connected to a pair of photomultipliers (PMTs), allowing continuous monitoring of the activity. This idea is the basis of the Waterrad detector, which can monitor radioactivity at environmental levels in river water. This paper describes the optimization of a detection cell containing PSm, a detection chamber as well as active and passive shielding. In its final set-up, the Waterrad detector presents a background signal of 0.23 (1) cps and detection efficiencies of 1.86(7)·10 −5 cps·L·Bq −1 for 3 H, 7.4(8)·10 −3 cps·L·Bq −1 for 90 Sr/ 90 Y and 5.5(5)·10 −3 cps·L·Bq −1 for 241 Am. The detection limits in the optimum window for a counting time of 5 h were 490 Bq/L for 3 H, 2.3 Bq/L for 90 Sr/ 90 Y and 3.0 Bq/L for 241 Am. These values indicate that Waterrad can be used as an alarm detector for monitoring radioactivity in water at activity levels similar to those of environmental samples, making it suitable for water or waste surveillance involving a high frequency of measurements. Graphical abstract: Image 1 Highlights: The development of a detector for the continuous monitoring of alpha and beta emitters in water samples is described. The detector is capable to detect 3 H, 241 Am and 90 Sr/ 90 Y with detection efficiencies of 0.6%, 61% and 159% respectively. DL are in the order of magnitude of the EU directive for drinking water for 3 H and gross beta for 5h counting. Waterrad detector is capable to perform automated analysis (including sample measurement, calibration and cell cleaning). Waterrad is designed to provide a fast alarm response since the minimum time of analysis is of 5 min.